Charcot-Marie-Tooth Disease 1X Simulating Paraparetic Guillain-Barre Syndrome. Issue 6 (November 2017) - Parissis, Dimitrios; Ioannidis, Panagiotis; Papadopoulos, Georgios; Karacostas, Dimitrios
Abstract : X-linked Charcot-Marie-Tooth disease (CMT 1X) is the second most common form of inherited demyelinating neuropathy. It is established that patients suffering from CMT 1X can have episodes of hemiparesis, paraparesis, quadriparesis, ataxia, aphasia, and dysarthria, which can be fully reversible, and 'trigger' factors for these episodes are usually febrile illness, high altitudes, hyperventilation, and physical activity. We describe a 22-year-old patient with a history of viral infection and sleep deprivation who presented to our department because of acute difficulty in walking and neurophysiological findings suggesting Guillain-Barre syndrome. The patient's phenotype was compatible with CMT disease and within hours he showed remarkable improvement of his muscle strength without receiving any medical treatment. Any other metabolic, infectious, vasculitic, hematological, paraneoplastic, or infiltrative cause of polyneuropathy was excluded with laboratory work-up. Diagnosis of CMT 1X was confirmed with repeated neurophysiological study and genetic testing of his and his mother's blood, demonstrating the Arg75Trp [CGG to TGG, (R75W)] mutation on exon2 of gap junction protein beta 1. CMT 1X should be considered in patients with a phenotype compatible with the disease, rapid improvement of their clinical manifestations, and neurophysiological findings consistent with a hereditary, demyelinating neuropathy.